Process selection methodology for service management in SME - Juan Luis Rubio Sánchez; Concepción Burgos García (Centro de Estudios Financieros, 2017)
It is a fact that more and more companies operations lay in information and communication technologies (ICT). Traditional management models need to be adapted to this new reality. That is why some initiatives are emerging (COBIT [control objectives for information and related technology], CMMI [capability maturity model integration], ITIL [information technology infrastructure library], etc.) which pretend to guide about the processes, metrics and technology management indicators most suitable. This document focuses in ITIL, that is the best representation of what has been called IT Governance. ITIL is a reference in technology services companies and in ICT departments of any company. That is due to the high level of utility provided by the organization and coverage of the processes proposed. Implantation of a management model based in ITIL processes forces companies to a relevant decision: which processes should be implemented?, which one should be the first one?, etc. The answer to this and other questions is not easy because the adoption of these processes implies an economical investment. This article shows an approach to the implementation order so we can optimize the position of the company in front of the competence in its sector, in front of similar sized companies or any other parameter we could define.